Implementasi Akad Produk Tabungan Rencana di PT. Bank Syariah Mega Indonesia Gallery Cianjur - Wanto, Muhammad (IAIN Salatiga, 2014)
Mudharabah savings is one product collector of funds applied to PT. BankSyariah Mega Indonesia Gallery Cianjur which one is the product SavingsPlan. On the product Savings Plan in PT. Bank Syariah Mega Indonesia GalleryCianjur use mudharabah product and in doing transactions through bookSavings Savings Plan Home / parent who uses contract wadiah. That mechanism Savings Plan held by PT. Bank Syariah Mega IndonesiaGallery Cianjur is (1) Fill out the application form Individual customers /Institutions; (2) Fill out the contract form wadiah (primary Savings); (3) Fillout the deposit slip early; (4) Fill out the form mudharabah (Savings Plan); (5)Customer Savings Plan (mudharabah) regularly to conduct the transactionto go through Main Savings account book / parent use wadiah agreement;(6) Facilities Savings Plan that is certified as proof of ownership savingsand checking account books as a book report. Legal basis in the productSavings Plan (mudharabah) No DSN. 02/DSNÂMUI/IV/2000 on Saving.In perspective muamalah two covenants in the transaction was prohibited.In practice the contract products Savings Plan (mudharabah) it looks likethere are two covenants in the transaction, the results of that research in thecontract mechanism problems Savings Plan product in PT. Bank SyariahMega Indonesia Gallery Cianjur is procedural only from banks and are inaccordance with the fatwa of DSN No.02 and there are no violations in fikihmuamalah.